The curse of King Tut's tomb, Merlin's Apprentice Double Feature Disc ([La Crosse, Wis.] : Echo Bridge Home Entertainment, 2008)
The curse of King Tut's tomb: The search for King Tut's tomb becomes a life-and-death struggle for two archaeologists - one who wants to protect the tomb's amazing powers and one who wants to use them to control the world
Merlin's apprentice: Hallmark's spectacular sequel to Merlin tells the story of Camelot, a once shimmering fortres of power and enchantment that has fallen from glory, and its heroic return to greatness
The curse of King Tut's tomb: The search for King Tut's tomb becomes a life-and-death struggle for two archaeologists - one who wants to protect the tomb's amazing powers and one who wants to use them to control the world.
The curse of King Tut's tomb: produced by Mitch Engel ; directed by Russell Mulcahy ; written by David Titcher
Merlin's apprentice: produced by Matthew O'Connor and Michael O'Connor ; directed by David Wu ; written by Christian Ford and Roger Soffer
The curse of King Tut's tomb: Casper Van Dien, Leonor Varela, Jonathan Hyde, Simon Callow, David Schofield, Malcolm McDowell
Merlin's apprentice: Sam Neill, John Reardon, Meghan Ory, Tegan Moss, Christopher Jacot, Garwin Sanford, Alexander Kalugin, Jennifer Calvert, Andrew Jackson, Duncan Fraser, Miranda Richardson
DVD
Keywords: Tutankhamen, -- King of Egypt -- Drama; Archaeologists -- Drama; Blessing and cursing -- Drama; Egyptologists -- Drama; Tombs -- Egypt -- Drama; Merlin (Legendary character) -- Drama; Grail -- Drama; Camelot (Legendary place) -- Drama; Egypt -- Drama